1990
DOI: 10.1113/jphysiol.1990.sp017902
|View full text |Cite
|
Sign up to set email alerts
|

Ca2(+)‐activated K+ current involvement in neuronal function revealed by in situ single‐channel analysis in Helix neurones.

Abstract: SUMMARY1. The properties of single calcium-activated potassium channels (or C-channels) were studied in cell-attached patches using the patch-clamp technique. Experiments were performed on identified Ca2+-dependent U cells in juvenile specimens (1-2 months old) of Helix aspersa.2. The criteria used to identify C-channels were based on comparison between macroscopic C-currents and currents reconstructed from unitary recordings. Both currents had a slow activation rate at large positive potentials which turned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 62 publications
7
27
0
Order By: Relevance
“…In spite of the slow time course of the macroscopic current, recordings of unitary currents in cell-attached patches have shown that the BK channel opening probability peaks within a few milliseconds of the spike upstroke at values as large as 0'25-04 (Lang & Ritchie, 1987;Gola et al 1990). These findings suggested that whole-cell BK currents observed under voltage clamp conditions did not give reliable information on their involvement in freely firing cells, presumably because of the way Ca2+ ions enter the cell in these different situations (see below).…”
Section: Kca Channels In Helix Neuronesmentioning
confidence: 99%
See 3 more Smart Citations
“…In spite of the slow time course of the macroscopic current, recordings of unitary currents in cell-attached patches have shown that the BK channel opening probability peaks within a few milliseconds of the spike upstroke at values as large as 0'25-04 (Lang & Ritchie, 1987;Gola et al 1990). These findings suggested that whole-cell BK currents observed under voltage clamp conditions did not give reliable information on their involvement in freely firing cells, presumably because of the way Ca2+ ions enter the cell in these different situations (see below).…”
Section: Kca Channels In Helix Neuronesmentioning
confidence: 99%
“…Its opening is dependent on both voltage and calcium ). According to Kostyuk, Doroshenko & Tsyndrenko (1980) and Lux & Hofmeier (1982) (Muller, Swandulla & Lux, 1989;Gola et al 1990). In the following experiments we reevaluated these hypotheses by correlating the activation rate of the macroscopic KCa current with the size of the underlying Ca2+ current.…”
Section: Firing Characteristics Of Ut Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the amphibian neuromuscular junction charybdotoxinsensitive channels normally decrease the duration of the terminal action potential and thereby determine the extent of calcium entry into the terminal, and therefore the amount of transmitter released (Robitaille & Charlton, 1992). This process is facilitated by the Ic channels being placed in the vicinity of the high density of calcium-channels that are strategically positioned at the release sites (Roberts et al, 1990;Gola et al, 1990;Robitaille & Charlton, 1992). NO blocks high-voltage threshold calcium channels in the ciliary ganglion (Khurana & Bennett, 1993) as well as blocking calcium influx in smooth muscle (Magliola & Jones, 1990;Clapp & Gurney, 1991).…”
Section: Discussionmentioning
confidence: 99%